Understanding the Fluid Nature of Personhood – the Ring Theory of Personhood. (19th February 2014) - Radha Krishna, Lalit Kumar; Alsuwaigh, Rayan
Abstract Familial determination, replete with its frequent usurping of patient autonomy, propagation of collusion, and circumnavigation of direct patient involvement in their own care deliberations, continues to impact clinical practice in many Asian nations. Suggestions that underpinning this practice, in Confucian‐inspired societies, is the adherence of the populace to the familial centric ideas of personhood espoused by Confucian ethics, provide a novel means of understanding and improving patient‐centred care at the end of life. Clinical experience in Confucian‐inspired Singapore, however, suggests that personhood is conceived in broader terms. This diverging view inspired a study of local conceptions of personhood and scrutiny of the influence of the family upon it. From the data gathered, a culturally appropriate, clinically relevant and ethically sensitive concept of personhood was proposed: the Ring Theory of Personhood (Ring Theory) that better captures the nuances of local conceptions of personhood. The Ring Theory highlights the fact that, far from being solely dependent upon familial centric ideals, local conceptions of personhood are dynamic, context dependent, evolving ideas delineated by four dimensions. Using the Ring Theory, the nature of familial influences upon the four dimensions of personhood – the Innate, Individual, Relational and Societal – are examined to reveal that, contrary to perceived knowledge, conceptions of personhood within Confucian societies are not the prime reason for the continued presence of this decision‐making model but remain present within local thinking and practices as a sociocultural residue and primarily because of inertia in updating ideas.